Therapeutic potential of exosomes/miRNAs in polycystic ovary syndrome induced by the alteration of circadian rhythms - Chen, Wei-hong; Huang, Qiao-yi; Wang, Zhi-yi; Zhuang, Xuan-xuan; Lin, Shu; Shi, Qi-yang (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a reproductive dysfunction associated with endocrine disorders and is most common in women of reproductive age. Clinical and/or biochemical manifestations include hyperandrogenism, persistent anovulation, polycystic ovary, insulin resistance, and obesity. Presently, the aetiology and pathogenesis of PCOS remain unclear. In recent years, the role of circadian rhythm changes in PCOS has garnered considerable attention. Changes in circadian rhythm can trigger PCOS through mechanisms such as oxidative stress and inflammation; however, the specific mechanisms are unclear. Exosomes are vesicles with sizes ranging from 30–120nm that mediate intercellular communication by transporting microRNAs (miRNAs), proteins, mRNAs, DNA, or lipids to target cells and are widely involved in the regulation of various physiological and pathological processes. Circadian rhythm can alter circulating exosomes, leading to a series of related changes and physiological dysfunctions. Therefore, we speculate that circadian rhythm-induced changes in circulating exosomes may be involved in PCOS pathogenesis. In this review, we summarise the possible roles of exosomes and their derived microRNAs in the occurrence and development of PCOS and discuss their possible mechanisms, providing insights into the potential role of exosomes for PCOS treatment.